DETERMINANTS OF DISCLOSURE OF FINANCIAL REPORTING FRAUD AND ITS IMPACT ON THE COMPANY’S FINANCIAL PERFORMANCE AT COMMERCIAL BANKS LISTED ON THE INDONESIAN STOCK EXCHANGE - Wira Lestari; Riski Hernando; Rita Fitriyani (Ekonomi Islam, 2019)
Financial reporting fraud can occur in all organizational lines and the perpetrators can be found at the organizational structure level from the top management level to the middle level management. There are still many cases of financial reporting fraud found in banking institutions due to weak implementation of corporate governance which is indicated by weak internal supervision and weak ethical commitment. Financial reporting fraud committed by bank managers directly affects the survival / business of banking and causes a decrease in share prices and corporate reputation due to the impact of disclosure of financial statement fraudulent information that is known by the supervisory agency. Keywords: Ethical Commitment, Audit Committee, Internal Audit, Financial Reporting Fraud, Corporate Financial Performance.